A problem for the mechanistic account of computation - Haimovici, Sabrina (2013)
The mechanistic account of computation proposes that computational explanation is mechanistic, i.e. it explains the behavior and capacities of mechanisms in terms of their components and the functions and organization of those components. According to this account, computing systems are mechanisms that perform computations, that is, they process vehicles according to rules that are sensitive to certain vehicle properties. Despite the emphasis mechanists place on the structural description of mechanisms? components and activities, the description of computations does not rely on the structural individuation of components and activities, but only on their functional individuation. Concrete computations and their vehicles are not described in terms of detailed structural properties, but are instead characterized in a medium-independent way, that is, independently of the physical medium that implements the computation. Thus, the same specific computation can be implemented in different physical media, allowing the multiple realizability of computational systems. In this paper, I argue that the mechanistic account faces a dilemma. If computations and computational systems are individuated in functional terms, then computational explanations are elliptic mechanistic explanations, or mechanism sketches. But, according to mechanists, mechanism sketches are incomplete and explanatorily weak. Alternatively, for the computational explanation to satisfy the criteria for a good mechanistic explanation, we need a new way to individuate computations based on structural properties. However, as a result of this, multiple realizability will no longer be possible for computational systems